Theory and method in higher education research. Vol. 2 - Huisman, Jeroen; Tight, Malcolm (Theory and method in higher education research ;, 2016)
Higher education research is a developing field internationally, which is attracting more and more researchers from a great variety of disciplinary backgrounds within and beyond higher education institutions. As such, it is an arena within which a wide range of theories, methods and methodologies is being applied. This volume of Theory and Method in Higher Education Research contains contemporary contributions to international debates regarding the application and development of theory and methodology in researching higher education. Amongst the theories discussed are actor-network theory, institutional logics, strategic positioning and threshold concepts. In terms of method and methodology, contributions consider validity in qualitative research, measuring competences, international-comparative research, shadowing, participatory research and participant-centred approaches to interviewing.